2019
DOI: 10.1136/bjophthalmol-2018-313719
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel oxygen saturation is affected in uveitis associated with Vogt-Koyanagi-Harada disease

Abstract: AimsTo discover whether retinal vessel oxygen metabolism is affected in uveitis associated with Vogt-Koyanagi-Harada (VKH) disease.Methods41 patients with VKH disease (82 eyes) and 12 healthy subjects (24 eyes) matched in age and gender were prospectively evaluated. Retinal oxygen saturation and vessel calibre were measured with a non-invasive spectrophotometric retinal oximeter (Oxymap T1).ResultsIn healthy controls, mean arteriolar oxygen saturation (%) was 93.8±5.9 and venular saturation was 60.1±5.8. In ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…These reversible retinal oximetry changes may provide a deeper understanding of the underlying physiological changes and can be used to monitor patients with lipemia retinalis. The reversibility of retinal oxygen saturation with treatment has also been reported in patients with Vogt-Koyanagi-Harada disease (VKH) [ 24 , 25 ]. Results of oxygen saturation in untreated lipemia retinalis may be affected by some parameters.…”
Section: Discussionmentioning
confidence: 99%
“…These reversible retinal oximetry changes may provide a deeper understanding of the underlying physiological changes and can be used to monitor patients with lipemia retinalis. The reversibility of retinal oxygen saturation with treatment has also been reported in patients with Vogt-Koyanagi-Harada disease (VKH) [ 24 , 25 ]. Results of oxygen saturation in untreated lipemia retinalis may be affected by some parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Increased blood flow will raise the oxygen saturation in retinal arterioles and venules because less oxygen will be lost from per unit volume of blood (Hardarson et al 2009). In a previous study, we reported the mean oxygen saturation values in retinal arterioles and venules as well as the mean diameters of retinal arterioles and venules in healthy controls (Abu El‐Asrar et al 2019). In the present study, these values were comparable to that of healthy controls after immunosuppressive therapy at final follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that the retinal oxygen metabolism is altered in uveitis associated with VKH disease and that it might serve as a potential biomarker of the outcome (Abu El‐Asrar et al 2019). However, to the best of our knowledge, there has been no previous study to investigate the effect of immunosuppressive therapy on retinal vascular oxygen saturation and calibres in initial‐onset acute uveitis associated with VKH disease.…”
Section: Introductionmentioning
confidence: 96%
“…2016; Abu El‐Asrar et al . 2012, 2019, 2021a, 2021b). A total of 20 patients (40 eyes) with initial‐onset acute uveitis associated with VKH disease were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we demonstrated the presence of abnormal retinal oxygen metabolism and calibre of retinal vessels in patients with initial‐onset acute uveitis associated with VKH disease and that immunosuppressive therapy normalized these changes (Abu El‐Asrar et al . 2019, 2021b).…”
Section: Introductionmentioning
confidence: 99%